LEARNING DESIGN FOR LINEAR EQUATIONS IN TWO VARIABLES BASED ON THE PMRI APPROACH USING THE GOJEK CONTEXT FOR EIGHTH-GRADE STUDENTS - Jesika Dwi Putriani; Zulkardi Zulkardi; Ely Susanti; Meryansumayeka Meryansumayeka (Mathline : Jurnal Matematika dan Pendidikan Matematika, 2025)
This study aims to develop a learning trajectory to stimulate students in solving problems related to the topic of systems of linear equations in two variables (SPLDV), packaged in the form of student activity sheets. This research employs a design research method of the validation study type, consisting of preparing for the experiment, the design experiment, and retrospective analysis. The research was conducted with 37 students from class VIII.1 at SMPN 9 Palembang. Data were collected through documentation, field notes, student activity sheets, and interviews. The collected data were analyzed through data reduction, descriptive presentation, and conclusion drawing. This study resulted in the following learning trajectory: (1) Observing contextual problems related to SPLDV using the GoJek context, specifically the additional bonus for GoCar partners, (2) Students presenting data, including what is known and what is being asked from the problem. (3) Students create possible scenarios for the distances traveled by GoCar partners on weekdays (Monday–Friday) and Saturdays, (4) Students solve the problem, predict alternative solutions, and draw conclusions. The learning trajectory utilizing the GoJek context effectively aids students in understanding and resolving issues related to SPLDV.